THE EFFECT OF THE PHYSICAL THERAPY ON PAIN AND ACTIVITY OF DAILY LIFE IN THE KNEE OSTEOARTHRITIS - Gülcan Gürer; Ö. Faruk Şendur; Cavidan Ay (Archives of Rheumatology, 2005)
This study was performed to research the effects of physical therapy agents on pain and disability in patients with knee osteoarthritis. Eighty one patients (40 study group;41 control group) with bilateral primary knee osteoarthritis were enrolled in this study. Physical therapy agents (hot pack, conventional TENS, ultrasound [1 watt/cm2] and isometric exercises of their quadriseps muscles) were applied to the patients of the study group ten sessions during two weeks and diclofenac sodium 100 mg/day were given to every patient. The same medications without physical therapy were given to control group patients. Kellgren-Lawrence Scale was used to evaluate the knee X-rays of the patients. The pain levels were measured with visual analog scale and activity of daily life was evaluated by using Lequesne index. Painless walking distances of the patients were measured and recorded. These evaluations were performed three times before, middle and after therapy. In conclusion significant improvement was determined when all parameters were evaluated in both groups after therapy (p<0.001). Furthermore, more improvement was determined in the study group when compared with control group after therapy (p<0.05).